Performance Evaluation for Surface Run off to Drainage System Normalization at Campus in Jakarta, Indonesia - Ariyani, Dwi; Sari, Adrima; Tri Juniati, Atie; Untarti, Atiek; khaddafy, Aditya (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Drainage is an infrastructure that distributesrainwater from one location to another. On the campus of the Faculty of Engineering at Pancasila University, there are several points of water inundation. Several inundation points were identified based on direct monitoring and measurements at the study site. This study aimed to evaluate the effectiveness of an existing drainage system on campus. The design flood discharge was calculated using a rational method with a five-year return period. From the calculation of hydrology, hydraulics, and comparative analysis of the existing dimensions with the design flood discharge, it was determined that the eight existing channels were unable to accommodate the design flood discharge. Therefore, there are two alternatives for reducing run off discharge. The first is to redesign the drainage channel to improve its size of the drainage channel with a shape that follows the existing shape. The modification involved adjusting the channel height to meet the specified flood discharge requirements. The second alternative was the planning of the infiltration wells. These dimensions are based on the design run off flood discharge, and from the calculation results, the dimensions of the infiltration wells are 1.5 meters in diameter and 2.5 meters high, and four infiltration wells are needed is 4 infiltration wells to reduce the discharge of 1,638 m3/second.